Hematopoietic cell transplant for reversal of liver fibrosis in a pediatric patient with erythropoietic protoporphyria. (6th January 2021) - Hashmi, Saman K.; Harstead, Elaine; Sachdev, Mansi; Black, Dennis D.; Clark, Ian; Ortanca, Ibrahim; Triplett, Brandon M.; Talleur, Aimee C.
Abstract: Background: EPP is a rare disorder of heme biosynthesis in which patients present with disabling photosensitivity. A subset of patients develop severe liver disease with progressive liver failure necessitating an OLT. A HCT can potentially cure EPP by replacing the native bone marrow, which is the primary site of heme synthesis. However, due to concerns for inherent risks of treatment‐related toxicities, the use of HCT has been reserved for patients undergoing an OLT to avoid disease recurrence in the hepatic graft. Data for HCT in EPP are lacking, particularly in the pediatric population. Case (Methods/Results): We present the case of a 12‐year‐old patient with EPP photosensitivity and cirrhosis, whom we successfully treated with pre‐emptive allogeneic HCT, significantly improving the patient's quality of life. We used a matched‐unrelated donor bone marrow–derived graft. Our patient achieved full donor peripheral blood chimerism and has not had any evidence of GVHD. In addition to resolution of photosensitivity, our patient had reversal of liver fibrosis which we feel was largely due to intervention at an early stage of compensated cirrhosis. Conclusion: Our case highlights the successful application of a known RIC regimen to this rare disorder that was well tolerated with sustained donor engraftment. It also emphasizes the importance of timing for HCT in patients with EPP and liver fibrosis. HCT should be considered early in pediatric patients with EPP‐hepatopathy to prevent progression to liver failure and need for OLT with lifelong immunosuppression.